Groups Process and Practice - Corey, Marianne Schneider (Brooks/Cole, 2006)
Drawing on their extensive clinical experience in working with groups, Marianne and Gerald Corey provide a realistic approach to the blending of theory with practice in group work. This best-selling text has been updated with new examples, guidelines, insights, and ideas that demonstrate how group leaders can apply the basic issues and key concepts of the group process to a variety of groups. Offering up-to-date coverage of both the "what is" and the "how to" of group counseling, the Seventh Edition features a greater focus on group work with children, the elderly, issues in both women's and men's groups and in school settings